2007
DOI: 10.1001/archpedi.161.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Blood Pressure in Children

Abstract: No evidence exists that moderate to severe SDB in childhood increases the risk of elevated BP, and there is heterogeneity among published reports. Large and methodologically rigorous investigations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 47 publications
1
42
2
4
Order By: Relevance
“…Our findings are in contrast to a recently published meta-analysis concluding there was no relationship between OSA in childhood and elevated BPs [25] . This analysis included only 5 papers with the vast majority of BP measurements performed during wakefulness.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to a recently published meta-analysis concluding there was no relationship between OSA in childhood and elevated BPs [25] . This analysis included only 5 papers with the vast majority of BP measurements performed during wakefulness.…”
Section: Discussioncontrasting
confidence: 99%
“…72 Studies demonstrating significant results are more likely to be published, especially in Englishlanguage indexed journals, as opposed to studies presenting negative findings, which are more likely to be published in a local journal, often nonindexed. 73 In this study, the effect of allele frequency and the effects of the dominant, recessive, and additive models were estimated. In addition, the consistency of genetic effects across populations from different ethnicities was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity from the cardiovascular system a) A meta-analysis did not demonstrate an association between OSAS and blood pressure [78]. Four subsequent cross-sectional studies (class IV) identified a significant association [79][80][81][82], but one casecontrol study did not confirm this finding [83].…”
Section: Literature Reviewmentioning
confidence: 97%